2013
DOI: 10.1016/j.ntt.2013.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Structural Magnetic Resonance Imaging in an adult cohort following prenatal and early postnatal exposure to tetrachloroethylene (PCE)-contaminated drinking water

Abstract: This population-based retrospective cohort study examined Structural Magnetic Resonance Imaging (MRI) of the brain in relation to prenatal and early postnatal exposure to tetrachloroethylene (PCE)-contaminated drinking water on Cape Cod, Massachusetts. Subjects were identified through birth records from 1969 through 1983. Exposure was modeled using pipe network information from town water departments, a PCE leaching and transport algorithm, EPANet water flow modeling software, and Geographic Information System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Early life exposure to PCE was not associated with alterations in the brain structures as seen in structural neuroimaging studies 18 . In particular, no statistically significant differences were observed between exposed and unexposed subjects on measures of white and gray matter volumes and white matter hypointensities.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Early life exposure to PCE was not associated with alterations in the brain structures as seen in structural neuroimaging studies 18 . In particular, no statistically significant differences were observed between exposed and unexposed subjects on measures of white and gray matter volumes and white matter hypointensities.…”
Section: Resultsmentioning
confidence: 80%
“…Eligible subjects who completed the survey were also invited to participate in a clinical study comprised of neuropsychological tests to evaluate visuospatial abilities, attention and executive function, short-term memory, motor skills, academic achievement, omnibus intelligence and mood; vision exams to assess color discrimination and contrast sensitivity; and magnetic resonance imaging (MRI) to measure white and gray matter volumes and white matter hypointensities 1618 . Prior studies among adults suggested that these outcomes might be affected by early life exposure to solvents 2125 .…”
Section: Summary Of Methods Used In the Cape Cod Health Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The survey from contaminated sites supported by Superfund confirmed that around one quarter of the sites were contaminated by PCE and the concentrations were from several hundred micrograms per liter to over one hundred milligrams per liter or even pure PCE liquid in some sites . It is reported that chronic exposure to PCE can cause headache, sleepiness or unconsciousness, and negatively affect the liver, kidney, reproductive system and central nervous system (CNS) . In Europe, the Scientific Committee on Occupational Exposure Limits recommends for PCE an occupational exposure limit (8 h time‐weighted average) of 20 mg L −1 and a short‐term exposure limit (15 min) of 40 mg L −1…”
Section: Introductionmentioning
confidence: 99%
“…4 It is reported that chronic exposure to PCE can cause headache, sleepiness or unconsciousness, and negatively affect the liver, kidney, reproductive system and central nervous system (CNS). 5 In Europe, the Scientific Committee on Occupational Exposure Limits recommends for PCE an occupational exposure limit (8 h time-weighted average) of 20 mg L −1 and a short-term exposure limit (15 min) of 40 mg L −1 . 6 Consequently, it is necessary to exploit effective remediation techniques to treat PCE-contaminated groundwater and soils.…”
Section: Introductionmentioning
confidence: 99%